Symbolic consumption in digital games: an analysis model (Intercom - Brazilian Journal of Communication Sciences, 2023)
The article presents the Analysis Model of Symbolic Consumption in Digital Games, developed with theoretical and methodological contributions from the Semiology of Social Discourses, Game Studies and the Communication Model as a Symbolic Market. From the study of the production of meanings by players in digital entertainment games, the elaboration of the model developed the idea that symbolic consumption results from a succession of articulated movements ranging from reception sensu stricto to appropriation. Developed and applied in research that focused on the consumption of meanings of health, the model allowed not only to highlight the networks of meanings, but also that these networks intertwine discourses of physical and virtual life and that the different ways in which the senses are consumed vary according to different contexts and forms of player involvement. The methodological development allowed the creation of analytical categories for the study of symbolic consumption.
Keywords: Communication; Symbolic consumption; Discourse analysis; Digital games; Analysis model